The construction of the Neo-SMEFRI Index Model for single motherpreneurs facing pandemic - Abdul Rahim, Memiyanty; Abu Hasan, Norraidah; Abdul Aziz, Rozainun; Mohamed Shith, Mohd Sirajuddin Siswadi Putera; Hamizah Ahmad, Saidah (Faculty of Administrative Science and Policy Studies, 2024)
Single-mother entrepreneurs (SMPs) play a vital role in bolstering the economy through their entrepreneurial endeavors. Women's entrepreneurship, including that of single mothers, catalyzes economic empowerment, granting women financial autonomy, decision-making autonomy, and control over their economic assets. This empowerment not only benefits the individual but also yields positive societal outcomes, as empowered women are more likely to invest in the education, health, and well-being of their families and future generations. This study aims to construct the Neo-SMEFRI Index Model (Single Motherpreneurs Financial Management and Resources Resilience Index) using the resource based view theory as a basis and to extend the theory for index formulation and construction. The specific objective for this paper are to come out with the new index that can be used by the government or any institutions in the authority to analyse the readiness score or level of single motherpreneurs in facing pandemic using certain measures. The index model has been formulated via three stages of data collection. The outcome of this study would help authorities via results from Neo-SMEFRI Index to discover the seriousness level of single motherpreneurs in term of entrepreneurial financial literacy, financial knowledge, self-efficacy, and resilience response in facing and coping with pandemic. This new index shall be used by other researchers from other countries for an ideal reference in knowing the status of single motherpreneurs resilence response level for their countries.